О взаимодействии субъектов экономической деятельности и формальные модели биоценоза - Заславский, В.А.; Киреев, С.А.; Ненахов, Э.И. (Теорія оптимальних рішень, 2004)
This work deals with the classification of subjects of the economic activities, constructed at the same principles as classification of biocenose is considered. The examples of models and results of the computer experiment for mutual relations such as "victim - exploiter" is calculated.